Adiponectin receptor PAQR-2 signaling senses low temperature to promote C. elegans longevity by regulating autophagy - Yuan-Li Chen (Nature Portfolio, 2019)
Decreased temperatures lengthen C. elegans lifespan by mechanisms that are not fully understood. Here the authors show that autophagy activation contributes to lifespan extension at low temperatures and that this involves adiponectin receptor PAQR-2 signaling.